ANALISIS TINGKAT KESEHATAN BANK DENGAN RISK PROFILE, GCG, EARNINGS DAN CAPITAL (RGEC) TERHADAP NILAI PERUSAHAAN BANK KONVENSIONAL - Penia Marsella, Penia (2021)
This study is a study that aims to determine the effect of bank soundness with Risk Profile, Good Corporate Governance, and Capital on Firm Value at Conventional Banks listed on the Indonesia Stock Exchange for the period 2017 to 2019. The sampling technique used in this study is purposive. sampling. This study used 40 samples based on predetermined criteria. Analysis of the data in this study using Microsoft Excel 2010, and hypothesis testing using panel data regression analysis with the Eviews version 11.0 program with a significance level of 5%. The results of this study are (1) Profile Risk using Non Performing Loan has no effect on firm value, (2) Good Corporate Governance (GCG) has no effect on firm value, (3) Return on Assets (ROA) has a negative effect on firm value. , (4) Capital Adequacy Ratio (CAR) has a positive effect on firm value.